Employee Engagement as a Strategic Capability in SMEs: An Applied Study in a Philippine Municipality - CATAYOC, RABEL (Universitas Airlangga, 2026)
This study investigated employee engagement as a strategic human resource capability among small and medium enterprises (SMEs) in a second-class municipality in the Philippines. Grounded in Social Exchange Theory, Herzberg’s Motivator-Hygiene Theory, and Sirota’s Three-Factor Theory, the research explores how employees perceive engagement across six domains: the work itself, compensation and benefits, work environment, leadership, opportunities for personal growth, and opportunities to contribute. Using a quantitative descriptive design, data were collected from 160 purposively selected SME employees through validated Likert-scale questionnaire. Results revealed consistently high engagement levels across all domains, with particularly strong scores in meaningful work and participatory opportunities. However, domain-specific gaps were noted in performance feedback, recognition, autonomy, and benefit delivery. ANOVA results indicated statistically significant differences in engagement based on education, job roles, compensation, length of service, and access to government-mandated benefits. These findings underscore the need for tailored engagement strategies in SMEs. In response, the study developed a Strategic Employee Engagement Matrix—an actionable framework featuring domain-specific goals, strategies, responsible departments, and multi-method evaluation tools. This matrix enables SMEs to align HRM practices with workforce expectations and business goals. The study concludes that employee engagement is not merely an HR metric but a strategic capability, particularly vital in resource-constrained SME environments. The findings contribute to both scholarship and practice by offering a replicable engagement model for local enterprises seeking to enhance workforce motivation, retention, and organizational resilience.